Growth and Identification of Bacteria in N-Halamine Dental Unit Waterline Tubing Using an Ultrapure Water Source - Nuala Porteous; Jie Luo; Monica Hererra; John Schoolfield; Yuyu Sun (International Journal of Microbiology)
This study examined bacterial growth and type on biofilm-controlling dental unit waterline (DUWL) tubing (T) and control manufacturer's tubing (C) in a laboratory DUWL model using ultrapure source water that was cycled through the lines. Sections of tubing lines were detached and examined for biofilm growth using SEM imaging at six sampling periods. Bacteria from inside surfaces of T and C, source unit, and reservoir were cultured and enumerated. At six months, organisms were molecularly identified from the alignment matches obtained from the top three BLAST searches for the 16S region. There was a 1–3 log increase in organism growth in a clean, nonsterile reservoir within an hour. Biofilm was established on the inside surfaces of C within three weeks, but not on T. Proteobacteria, and Sphingomonas spp. were identified in the source reservoir and C line, and a variation of the genera was found in T line.